Effects of Aerobic Strength Training on Physical Fitness and Weight Loss of Female University Students - Junaid Riaz; Kai Ma; Nabila Sharif; Nerges Batool (The Sky, 2024)
There is still a growing global trend of physical inactivity despite several research showing the positive effects of exercise on health. Furthermore, the most effective weight-loss or weight-control approach is still in debate. The literature has proven that suggested aerobic strength training (AST) enhances a variety of physical performance outcomes in sports, which helps to validate the effectiveness of AST on physical fitness and weight reduction. Even though AST is one of the most popular strength training techniques, more research is needed to fully understand how it affects female university students’ ability to lose weight and perform physically. The purpose of this study was to test the impact of 8 weeks of aerobic strength exercises in female students for physical fitness and weight loss. The study sample comprised overall female students of the Islamia University of Bahawalpur (Baghdad-ul-jaded Campus). The participants of the study were (n = 30) females with ages between (M = 25.45; SD = 30.58 years) were divided into two groups: The experimental group (EG; n=15), and the control group (CG; n=15). Prior to and after the intervention, participants experienced physical and anthropometric measurements. Data were analyzed by applying descriptive, paired sample t-test, and independent t-test. Only a significant improvement for Left Hand Grip Strength (LHGS) (p = 0.05), Agility (p = 0.00), Flexibility (p = 0.01), Skipping (p = 0.01), 30-m Shuttle Run Test (p = 0.00) Were found in all physical fitness parameters and participants significantly losing weight for the EG (p<0.05) As compared to the control group. The findings suggest that AST improves female students’ physical fitness and helps to reduce weight.